Conflict, food price shocks, and food insecurity: The experience of Afghan households - Anna D'Souza; Dean Jolliffe (Institute for the Study of Labor (IZA), 2012)
Using nationally-representative household survey data and confidential geo-coded data on violence, we examine the linkages between conflict, food insecurity, and food price shocks in Afghanistan. Spatial mappings of the raw data reveal large variations in levels of food insecurity and conflict across the country; surprisingly, food insecurity is not higher in conflict areas. In a multivariate regression framework, we exploit the 2008 spike in wheat flour prices to estimate differential effects on household food security - measured by calorie intake and the real value of food consumed - based on the level of conflict in the province where the household is located. We find robust evidence that households in provinces with higher levels of conflict experience larger declines in food security than households in provinces with lower levels of conflict. Therefore while conflict may not be the driving factor in overall levels of food insecurity in Afghanistan, it may limit the coping mechanisms available to households in the face of rising food prices. Gaining a better understanding of such linkages and knowing the spatial distribution of food insecurity can serve to inform policymakers interested in targeting scarce resources to vulnerable populations, for example, through the placement of strategic grain reserves or targeted food assistance programs.
Keywords: D12; I3; O12; 330; Afghanistan; food security; conflict; nutrition; poverty; spatial distribution; Politischer Konflikt; Politische Gewalt; Nahrungsmittelversorgung; Nahrungsmittelpreis; Schock; Armut; Räumliche Verteilung; Afghanistan